2013
DOI: 10.1017/sjp.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Learning of Facial Responses to Faces Associated with Positive or Negative Emotional Expressions

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription Spanish Journal of PsychologyFaces and facial expressions of emotion have a critical role in human social interaction. Being able to extract socially relevant information from faces and to decode the meaning of facial expressions is crucial for a proper understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Interestingly, even a pairing of a person's neutral face with an emotional expression of that same person changes the reactions to that person's neutral face. Aguado et al ( 2013 ) presented neutral static expressions and immediately thereafter a happy or angry static expression shown by the same persons. They found that participants who reacted with a differential pattern, i.e., higher Corrugator activation to angry than happy faces and higher Zygomaticus activation to happy than angry faces, showed this differential pattern already to the neutral faces of the respective persons in the second half of the experiment.…”
Section: The Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, even a pairing of a person's neutral face with an emotional expression of that same person changes the reactions to that person's neutral face. Aguado et al ( 2013 ) presented neutral static expressions and immediately thereafter a happy or angry static expression shown by the same persons. They found that participants who reacted with a differential pattern, i.e., higher Corrugator activation to angry than happy faces and higher Zygomaticus activation to happy than angry faces, showed this differential pattern already to the neutral faces of the respective persons in the second half of the experiment.…”
Section: The Relationshipmentioning
confidence: 99%
“…As soon as individuals actually interact, they learn about each other (see Hofman et al, 2012 ; Aguado et al, 2013 ), which can, in turn, rectify pre-existing assumptions or change individuals' mood states. Factors such as the topic of the conversation, the facial mimicry of the sender, or the clarity, dynamic and type of facial signals will influence the emotional tone of the conversation and the cognitive and emotional states of the interaction partners.…”
Section: General Conclusionmentioning
confidence: 99%
“…When observing emotional faces, small responses in the facial muscles of the viewer take place in those muscles that are used for the expression of the emotion. For example, viewing happy human faces is accompanied with electromyography (EMG) activity in the zygomaticus major (ZM), the main muscle for expressing a smile, and viewing angry human faces evokes activity in corrugator supercilii (CS), the muscle for expressing a frown ( Dimberg and Petterson, 2000 ; Dimberg et al, 2000 ; Aguado et al, 2013 ). It has been shown that perceiving emotional CG avatar faces results in EMG activity in the same facial muscles as perceiving photographs of human faces, e.g., the ZM for happy avatar faces ( Weyers et al, 2006 ; Likowski et al, 2012 ) and the CS for sad and angry avatar faces ( Likowski et al, 2012 ).…”
Section: Perception Of Emotion In Virtual Characters and Robotsmentioning
confidence: 99%
“…For instance, Izard ( 2007 ) suggests the existence of six discrete basic emotions: interest, joy/happiness, sadness, anger, disgust, and fear. These theorists (e.g., Izard, 1993 ; Ekman, 1999 ) assume that basic emotions are outcomes of environmental adaptation and have distinctive facial units, physiology, and related behavioral tendencies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%